2020
DOI: 10.2334/josnusd.19-0005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a methacrylate monomer with a thiohydantoin structure

Abstract: The purpose of the current study was to synthesize a methacrylate monomer with a thiohydantoin structure. In a flask, (2-thiohydantoin-4-yl) propionic acid, 10-hyroxydecyl methacrylate, 4-dimethylaminopyridine, and tetrahydrofuran (THF) were placed in a nitrogen atmosphere. A THF solution of N,N'-dicyclohexylcarbodiimide was added and stirred at room temperature. Ethyl acetate and n-hexane were then added to the reaction mixture. The reacted slurry was purified by chromatography with silica gel and hexane-ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This study also highlights the utility of chemical techniques for developing and evaluating biomaterials, which have often a complex constitution with dozens of components [ 32 , 33 , 34 ]. Additionally, chemical reactions occur during their manipulation, application, and later when in contact with the living tissues [ 19 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also highlights the utility of chemical techniques for developing and evaluating biomaterials, which have often a complex constitution with dozens of components [ 32 , 33 , 34 ]. Additionally, chemical reactions occur during their manipulation, application, and later when in contact with the living tissues [ 19 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the VTD monomer was reported to exhibit high bonding durability when joined to type IV gold or silver-palladium-copper alloys, which was speculated to result primarily from interactions between the thione or thiol groups and copper elements contained in both alloys 10,13,19) . Previous studies have reported that the bonding mechanism of the VTD monomer to noble metal alloys involves an ionic interaction between mercapto groups in the VTD and metal ions in the alloys, especially gold, silver, or copper 33,34) . With respect to the bonding mechanism of the MDDT monomer with pure gold, Ikemura et al suggested that the cyclic disulfide group is cleaved at the disulfide bond or ring-opening and interacts with the gold atoms to form a sulfur-gold bond at the metal surface 15,18) .…”
Section: Discussionmentioning
confidence: 99%
“…The VP contained VBATDT monomer. MP was synthesized according to a previously described method 13) . Both primers were of a single liquid type and contained one adhesive monomer in the acetone.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, the synthesis of a novel sulfur-containing monomer, 10-methacryloyloxydecyl-(2-thiohydantoin-4-yl) propionate (MDTHP), was reported 13) . MDTHP is a monomer containing thiohydantoin, a five membered heterocyclic compound with a thione structure.…”
Section: Introductionmentioning
confidence: 99%